Recurrent Episodes of Paraphilic Behavior Possibly Associated With Olanzapine and Aripiprazole Treatment in a Patient With Schizophrenia - Stefanou, Maria-Ioanna; Vittore, Debora; Wolz, Ines; Klingberg, Stefan; Wildgruber, Dirk (Frontiers in Psychiatry, 2020)
Background: Hypersexual and paraphilic disorders have been frequently associated with concomitant psychiatric disorders, including schizophrenia. A growing number of published cases has recently indicated that hypersexual behavior may also arise in conjunction with treatment with second generation antipsychotics. Although hypersexuality has been acknowledged as a possible side effect of antipsychotic treatment with partial dopamine agonists, including aripiprazole, only very few cases of olanzapine-associated hypersexuality have been reported in the literature. Case Presentation: A 29-year-old man presented with delusions of persecution and reference, auditory hallucinations and negative symptoms, and was diagnosed with paranoid-hallucinatory schizophrenia. One and a half months after initiation of antipsychotic treatment with olanzapine, he developed compulsive sexual behavior and paraphilia, without signs of akathisia. After olanzapine discontinuation, a full remission of the hypersexual behavior was noted within one week, and treatment was switched to risperidone. Due to hyperprolactinemia, adjunct treatment with low-dose aripiprazole was initiated and a severe recurrence of identical hypersexual behavior occurred. The hypersexual behavior resolved completely within a week after aripiprazole discontinuation. Conclusion: This case illustrates that hypersexuality may be a rare adverse effect of treatment with second generation antipsychotics. Although aripiprazole is a drug with a well-established risk for hypersexuality, the question of whether a causal association between hypersexuality and olanzapine exists remains currently unresolved. As the currently limited amount of available evidence precludes any definitive conclusions, additional research is warranted to delineate the possible neurobiological substrates of hypersexual and paraphilic disorders in patients treated with second generation antipsychotics.